PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA UMKM DAWET IRENG DELIMA DAN DELIMA SNACK - Olivia Riska Ramadhani; Martinus Budiantara (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to improve the financial management capabilities of MSMEs actors through the implementation of simple financial statement preparation. The background of this activity is based on the low awareness of business owners regarding the importance of recording every transaction, resulting in the lack of specific financial information. The program was conducted at Dawet Ireng Delima MSMEs and Delima Snack MSMEs. The method began with interviews to identify existing financial management practices, followed by assistance in preparing simple financial statements, and evaluation to assess the implementation results. The results indicate an improvement in the understanding and skills of MSMEs actors in recording financial transactions in a structured manner, enabling clearer information on income and expenses. These findings show that systematic assistance in preparing simple financial statements can sustainably enhance MSMEs’ financial management capabilities.